Why Do Sellers Hold Out in the Housing Market? An Option‐Based Explanation. (1st November 2012) - Qian, Wenlan
<x xml:space="preserve">Abstract</x> In the residential housing market, home owners are reluctant to sell in a declining market. We build a model which focuses on the embedded call option associated with home ownership that allows owners to delay the (irreversible) sale. When prices are low, the (opportunity) cost of a sale, i.e., a higher implied gain from a future sale, likely exceeds its immediate trade benefit and an owner is better off waiting for market conditions to improve. The model also highlights the importance of supply conditions: a more constrained supply is associated with a longer delay. Using state‐level residential housing data, we find evidence consistent with the model. Transaction volume is increasing (decreasing) in the rental growth rate (volatility) in the cross section; their effects are amplified in areas with low supply elasticities, and in times with low market prices. Overall, this paper provides a rational explanation for delayed trading decisions in the housing market.